Prevalence and antimicrobial susceptibility pattern of Salmonella and Shigella in stool among patients presenting with diarrhea in a tertiary care centre in south India - Arun Sachu (Iranian Journal of Microbiology, 2023)
Background and Objectives: Bacterial causes of gastroenteritis include Salmonella, Shigella spp, diarrheagenic Escherichia coli, Vibrio cholera and Campylobacter spp. Although infections caused by NTS (Non Typhoidal Salmonella) and Shigella are usually self-limiting, antibiotic treatment is prefered in severely ill or immunocompromised individuals. The main objective of the study was to find out the prevalence of Salmonella and Shigella among the stool samples received in Believers Church Medical College hospital and the antimicrobial susceptibility pattern of Salmonella spp. and Shigella spp. Materials and Methods: A total of 805 stool samples collected from cases of diarrhea from January 2018 to December 2021 were processed in the laboratory. Standard bacteriological methods were used to isolate, identify, and determine the antimicrobial susceptibility pattern of Salmonella and Shigella isolates using the disc diffusion method and interpreted according to CLSI. Results: A total of 100 (12.4%) samples yielded bacterial pathogens. Salmonella was isolated from 97 (12%) samples and Shigella from 3 (0.4%) samples. Salmonella enterica serovar Typhimurium was the predominant serotype, accounting for 53 (54.6%) isolates. Conclusion: This study showed Salmonella enterica serovar Typhimurium as the predominant isolate causing diarrheal illness. The emergence of multidrug resistant phenotypes warrants the continuous monitoring of susceptibility trend of NTS in India.